2007
DOI: 10.1111/j.1464-410x.2007.07221.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the vesico‐urethral anastomosis after radical retropubic prostatectomy: transrectal ultrasonography can replace cystography

Abstract: OBJECTIVE To determine if transrectal ultrasonography (TRUS) is as reliable as cystography in detecting vesico‐urethral extravasation (VE) after radical retropubic prostatectomy (RRP). PATIENTS AND METHODS Between October 2005 and February 2006 we prospectively investigated 100 consecutive patients undergoing RRP. The vesico‐urethral anastomosis was assessed 6 days after RRP by a combined investigation with TRUS and cystography. RESULTS In most patients (79%), at 6 days after RRP the vesico‐urethral anastomosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 11 publications
(16 reference statements)
0
18
0
2
Order By: Relevance
“…However, this small difference would most likely be clinically insignificant given our relative low percentage of leak. Studies have shown that a majority (79 to 95%) of patients undergoing radical prostatectomy do not have a urine leak by cystogram seven days postoperatively (13)(14)(15). By 15 to 21 days after surgery, nearly 100% of patients do not have a urinary leak at the UVA (13,16).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this small difference would most likely be clinically insignificant given our relative low percentage of leak. Studies have shown that a majority (79 to 95%) of patients undergoing radical prostatectomy do not have a urine leak by cystogram seven days postoperatively (13)(14)(15). By 15 to 21 days after surgery, nearly 100% of patients do not have a urinary leak at the UVA (13,16).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that a majority (79 to 95%) of patients undergoing radical prostatectomy do not have a urine leak by cystogram seven days postoperatively (13)(14)(15). By 15 to 21 days after surgery, nearly 100% of patients do not have a urinary leak at the UVA (13,16). The type or number of sutures used has not seemed to affect urinary leak rates, suggesting that the most important factor in a leak-free UVA is good tissue approximation and an intraoperative watertight closure.…”
Section: Discussionmentioning
confidence: 99%
“…Eggert et al [10] reported a sensitivity of 100% and specificity of 97.5% using a TRUS for assessing the urinary leakage at the VUA site on postoperative day 6 in a series of 100 men undergoing RRP. Schenck and Schneider [11] developed a new method for evaluating the VUA using a dynamic TRUS with bladder filled only with NaCl 0.9% on postoperative days 4-8.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, ultrasound has emerged as an interesting alternative diagnostic tool for evaluating the urinary leakage at the VUA site. It could be performed by the urologist and easily repeated, there is no exposure to radiation, it is useful for the evaluation of any hematomas or lymphoceles and it has low costs [10]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation